Challenges in applying expert systems to the investment-construction projects designing - Uvarov, Pavlo; Tatarchenko, Galina; Shparber, Marina; Biloshytska, Natalia (Academic journal Industrial Machine Building Civil Engineering, 2020)
He design systematology possibilities in investment and construction activity tasks maintenance with engineering decisions acceptance quality estimation based on organizational and technological designing expert systems are studied. In the research course, the using challenges the expert systems for investment-construction production organizational and technological design were considered. The assessing quality principles and possibilities engineering decisions and intellectualization of the economic analysis functions for investment-construction projects planning and management are formulated. Knowledge scientific and engineering support methods bases and data are offered
Keywords: investment-construction projects; expert systems for organizational and technological design; design systemology; general engineering; database